Coexistence of acrokeratoelastoidosis and knuckle pad‐like lesions. Issue 1 (14th February 2022) - Navarro‐Bielsa, Alba; Gracia‐Cazaña, Tamara; Abadías‐Granado, Isabel; Conejero del Mazo, Raquel; Gilaberte, Yolanda
Abstract: Acrokeratoelastoidosis (AKE) is a marginal papular keratoderma. It is a rare autosomal dominant condition that may also present in childhood or adulthood in sporadic cases. AKE is distinguished by its histological findings, with dermal elastorrhexis and an overlying epithelial dell. We report a 55‐year‐old woman with AKE and knuckle pads on the palms and soles, which are considered as an extension of AKE papules to the interphalangeal joints.